Conocimientos tradicionales sobre el embarazo, parto y post parto en la comunidad nativa Ticuna Cushillo Cocha, provincia Mariscal Ramón Castilla 2024 - Candido Yumbato, Alonso (2025)
The primary objective of this final report was to describe traditional knowledge about pregnancy, childbirth, and postpartum care from the practices of women in the Ticuna indigenous community of Cushillo Cocha. The research was qualitative, descriptive, and ethnographic in design. The sample consisted of 20 families, comprised of pregnant women and their husbands, midwives, and community authorities from the Tikuna indigenous community located in the Caballo Cocha district, specifically in Cuchillo Cocha. The anthropological field techniques used were participant observation, ethnographic work, and semi-structured interviews. Pregnancy in Cushillo Cocha is experienced as a liminal state, where the body becomes a sacred channel. The beliefs surrounding it structure practices, emotions, and behaviors that resist hegemonic medicalization. Far from being isolated superstitions, this knowledge constitutes a coherent cultural system that articulates biology, spirituality, and community. This work concludes by demonstrating that traditional knowledge about pregnancy, childbirth, and postpartum in the Ticuna community of Cushillo Cocha constitutes a medical system with its own logic and efficacy, deeply rooted in a worldview that articulates the biological, spiritual, and social aspects.